DEVELOPMENT OF ALMAJRITI (APLIKASI MATEMATIKA JAGO PROGRAM LINIER INTERAKTIF) FOR CLASS XI STUDENTS OF SENIOR HIGH SCHOOL - Nisa', Asfira Zakiatun; Marhayati, Marhayati; Chandra, Faizal (Jurnal Pendidikan Matematika (JUPITEK), 2022)
This research aims to develop a valid ALMAJRITI (Aplikasi Matematika Jago Program Linier Interaktif) learning media and to determine student responses. Student responses were obtained from questionnaires and tests (pre-test and post-test). The study conducted is in the form of R&D with ADDIE steps. Media, learning, material, IT (Information Technology), language, and practitioners experts validate the media. The validation results obtained from each validator sequentially are 100% (very valid), 85% (very valid), 84.62% (very valid), 70% (valid), 87.5% (very valid), 96 ,87% (very valid). The media is very valid if it gets 75% or more. Overall, the media obtained a very valid assessment result of 87.33%, so the media was feasible to use. Meanwhile, the test instrument was validated by a material expert. The media was tested in class XI IPA 3 MAN 1 Blitar. The use of media shows a positive student response. More than 65% of students gave a positive response based on the questionnaire results. In addition, the average pre-test was 17.07, the post-test was 77.5, and the percentage increase in student learning outcomes was 405%. Thus, there is an increase in student learning outcomes before and after using ALMAJRITI. This increase shows a positive response from students to the ALMAJRITI. Therefore, it can be concluded that the ALMAJRITI media is valid and feasible to be used as a learning resource for class XI students